Degradative enzymes and biosurfactant mediated mechanism of diesel fuel and n-hexadecane biodegradation by Paenibacillus sp. D9. Issue 4 (15th June 2022) - Jimoh, Abdullahi Adekilekun; Lin, Johnson
Abstract: Hydrophobic pollutants remain a serious threat to animals, plants, humans, and the biological system at large if not reduced or removed from the environments. This study focused on the experimental degradation analysis of 2% each of diesel fuel and n- hexadecane utilized as a source of carbon and energy by Paenibacillus sp. D9. During the process, there was the removal of 98.4% and 61.2% n -hexadecane and diesel fuel, respectively, in the 14 days incubation period. There was involvement of degradative enzymes, namely alkane hydroxylase, alcohol dehydrogenase, and esterase as determined during the process of biodegradation. The activities of alkane hydroxylase (82 U), alcohol dehydrogenase (23 U), and esterase (0.220 U) were differentially produced, with enhanced biosurfactant activity, demonstrating their contribution to degradation of hydrocarbons. The outcomes were additionally reinforced as specific polymerase chain reaction primers were used to detect the presence of genes responsible for biodegradation and biosurfactant synthesis. The data revealed that the efficiency of the biosurfactant in accelerating the degradation and solubilization of these hydrocarbons was ensured with high hydrophobicity, emulsifying capacities, and surface tension reduction. Therefore, due to the production of enzymes, Paenibacillus sp. D9 strain was active than reported biosurfactant-producing bacteria in the biodegradation of hydrophobic pollutants.